A new Drosophila model of prolonged inactivity shortens lifespan and impairs muscle function - Jodi Protasiewicz; Sarah Snider; Mousumee Khan; Li Tao; Robert J. Wessells; Alyson Sujkowski (Scientific Reports)
Abstract Prolonged inactivity due to medical conditions can cause chronic muscle disuse and lead to physical incapacity and poor quality of life. Here, we developed a Drosophila model of confinement inactivity (CI) to observe its effects on lifespan and muscle function. We found that, similar to mammalian models and humans, CI negatively impacted longevity and function in Drosophila. Confined flies had impaired mobility, shorter lifespan, and reduced muscle integrity compared to their freely mobile siblings. These findings establish a new, highly efficient platform for studying long term effects of chronic sedentary behavior and muscle disuse in the genetically tractable Drosophila model. In addition, we found that temporarily removing flies from CI for scheduled bouts of forced physical exercise ameliorated negative effects, in part by improving muscle homeostasis. Finally, we tested whether muscle overexpression of 3 exercise-responsive genes, dPGC-1α, dFNDC5, or dSesn, could prevent the negative impact of CI on fly aging, even without physical exercise. We previously established that overexpression of these factors phenocopies exercise effects in aging wild-type and disease model flies. We found that when overexpressed in muscle, dSesn prevented premature declines in endurance, and dFNDC5 protected speed and endurance. This new model can be used in the future for mechanistic studies to identify preventative and therapeutic targets for diseases associated with chronic inactivity.